2017
DOI: 10.3389/fmicb.2017.01811
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Adaptation of Listeria monocytogenes to Lagoon and Soil Matrices Associated with a Piggery Environment: Comparison of Expression Profiles

Abstract: Understanding how Listeria monocytogenes, the causative agent of listeriosis, adapts to the environment is crucial. Adaptation to new matrices requires regulation of gene expression. To determine how the pathogen adapts to lagoon effluent and soil, two matrices where L. monocytogenes has been isolated, we compared the transcriptomes of L. monocytogenes CIP 110868 20 min and 24 h after its transfer to effluent and soil extract. Results showed major variations in the transcriptome of L. monocytogenes in the lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 108 publications
2
14
0
Order By: Relevance
“…Similarly, consistent with limited availability of amino acids, 15 genes of the regulon of CodY, a repressor of branched chain amino acid biosynthesis, were upregulated at all timepoints following instillation of L. monocytogenes into soil (37). In a follow up study with different soil, upregulation of PTS systems was also observed, including those for cellobiose, mannitol and maltose, among others (38). Finally, both of these studies observed repression of genes regulated by the master virulence regulator, PrfA, consistent with the longstanding observation that in the presence of PTS substrates PrfA expression is repressed (39).…”
Section: Life As a Saprophytesupporting
confidence: 52%
“…Similarly, consistent with limited availability of amino acids, 15 genes of the regulon of CodY, a repressor of branched chain amino acid biosynthesis, were upregulated at all timepoints following instillation of L. monocytogenes into soil (37). In a follow up study with different soil, upregulation of PTS systems was also observed, including those for cellobiose, mannitol and maltose, among others (38). Finally, both of these studies observed repression of genes regulated by the master virulence regulator, PrfA, consistent with the longstanding observation that in the presence of PTS substrates PrfA expression is repressed (39).…”
Section: Life As a Saprophytesupporting
confidence: 52%
“…Two formate transporters (lmo0593, lmo0912) and a fumarate reductase (lmo0355) were downregulated explained by the evidence of formate being a metabolic end product only seen during anaerobic growth (Romick et al, 1996). In line with the upregulation during desiccation of glutamine transporters, glnR (lmo1298), a glutamine synthase repressor (Vivant et al, 2017) was downregulated. The most downregulated gene (>13 fold) during desiccation were the predicted transcriptional regulator lmo2447 ( Table 3).…”
Section: Strain Independent Core Desiccation Stress Response In L Momentioning
confidence: 92%
“…Entry to the soil also causes prfA to be downregulated, subsequently deactivating key virulence factors while genes involved with mobility, chemotaxis and the transport of carbohydrates are upregulated (Vivant et al . ).…”
Section: Mechanisms Of L Monocytogenes Survival In Soilmentioning
confidence: 97%
“…SigB too plays an important role in soil survival-it regulates the stress response after L. monocytogenes entry to the soil allowing the bacteria to stop multiplying as a response to nutrient limitation, similar to entry to the stationary phase (Piveteau et al 2011). Entry to the soil also causes prfA to be downregulated, subsequently deactivating key virulence factors while genes involved with mobility, chemotaxis and the transport of carbohydrates are upregulated (Vivant et al 2017).…”
Section: Mechanisms Of L Monocytogenes Survival In Soilmentioning
confidence: 99%